1998
DOI: 10.1046/j.1365-2621.1998.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of freezing and thawing on the magnetic resonance imaging parameters of water in beef, lamb and pork meat

Abstract: A new multisample magnetic resonance imaging (MRI) technique has been used to measure the values of T1, T2, magnetization transfer (MT) rate and liquid proton density ratio (M0%) for water in fresh and frozen–thawed beef, lamb and pork; four samples from the longissimus dorsi muscle of 25 different individuals per species were studied. The effect of two different chilling regimes, standard and tenderloin, were also studied. Standard chilled pork and lamb had a significantly higher M0% than tenderloin chilled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 43 publications
(49 reference statements)
0
17
0
3
Order By: Relevance
“…For example, this property enables testing aseptically packaged foods for spoilage organisms ) (speed of realignment changes with spoilage) and to measure characteristics of foods (moisture, fat, and sugar contents, ripeness) . Also, water has been studied during freezing and thawing of beef, lamb and pork meat (Evans et al, 1998), water absorption in barley cultivars (McEntyre et al, 1998), in cheese during cooling , etc. The main advantages of MRI are that these systems are non-invasive and non-contacting.…”
Section: Image Analysis Techniques: Atomic Force Microscopy (Afm) Andmentioning
confidence: 99%
“…For example, this property enables testing aseptically packaged foods for spoilage organisms ) (speed of realignment changes with spoilage) and to measure characteristics of foods (moisture, fat, and sugar contents, ripeness) . Also, water has been studied during freezing and thawing of beef, lamb and pork meat (Evans et al, 1998), water absorption in barley cultivars (McEntyre et al, 1998), in cheese during cooling , etc. The main advantages of MRI are that these systems are non-invasive and non-contacting.…”
Section: Image Analysis Techniques: Atomic Force Microscopy (Afm) Andmentioning
confidence: 99%
“…Physical methods that can detect changes in dielectric properties include nuclear magnetic resonance (22), mag netic resonance imaging (14,29), fish freshness tester (26), and two-frequency impedance (6). Microbiological (41) and organoleptic (4) analyses also have been used.…”
mentioning
confidence: 99%
“…On the other hand, the frozen storage had no significant effect on the 2 shorter relaxation times, T 2 ′ and T 2 ″ observed in their study. Using MRI relaxation measurements, Evans and others (1998) showed that protein denaturation during freezing of meat was consistent with a decrease in the longitudinal relaxation time T 1 . It was suggested that an increase in molecular weight of the proteins, due to protein aggregation, would reduce the mobility of the proteins and enhance cross‐relaxation, thus reducing the T 1 value.…”
Section: Resultsmentioning
confidence: 99%